Long-Term Mortality for Patients of Primary Aldosteronism Compared With Essential Hypertension: A Systematic Review and Meta-Analysis - Meng, Zhe; Dai, Zhe; Huang, Kai; Xu, Chang; Zhang, Yin-Gao; Zheng, Hang; Liu, Tong-Zu (Frontiers in Endocrinology, 2020)
Abstract Background: Consistent evidence have demonstrated that patients with primary aldosteronism (PA) have higher risk of cardiovascular events to patients with essential hypertension (EH). Whether the long-term risk of mortality for PA patients is higher than EH patients is unclear. We aim to compare the long-term mortality of patients with PA to patients with EH. Methods: We searched PubMed, Embase, and Cochrane Central Register of Controlled Trials for eligible studies from inception to 14 Nov 2018. We combined the relative risks (RR) of each included study by random-effect model. The amount of between study heterogeneity was measured by the I2 statistic. Results: We totally included 6 studies with cohort design, including 3039 PA and 45495 EH patients. The pooled RRs for patients with PA were 1.97 (95%CI: 1.33, 2.91; P= 0.0007) for a follow-up of 3 years, 0.96 (95%CI: 0.75, 1.23; P= 0.76) for 5 years, 0.86 (95%CI: 0.51, 1.46) for 7.5 years, and 0.95 (95%CI: 0.61, 1.48; P= 0.58) for 10 years. For patients with aldosterone-producing adenomas (APA), evidence of lower risk of long-term mortality was observed. Our sensitivity analysis suggested our results were stable. Conclusions: Current evidence supported a higher risk of mortality for patients with primary aldosteronism at 3 years compared to patients with essential hypertension, however this risk no longer sustains as the follow-up time increased to 5 or more years. Patients with aldosterone-producing adenomas may have lower long-term mortality rate than patients with essential hypertension due to the better recovery of adrenalectomy.